Degradirana območja organizirane večstanovanjske gradnje med letoma 1945 in 1965 v Sloveniji - metodologija vrednotenja in prenove - Zupančič-Strojan, Tadeja (Urbani izziv, 2002)
'Degraded' housing areas represent a 9% share of urbanised surfaces of thirtyfive in planning terms recently researched Slovenian towns. Above all social housing estates built between 1945 and 1965 present issues since they are isolated, poorly maintained, and cannot reach modern standards. The research contemplates the redirecting of the present abstract planning rationales to the real architectural, user level. Further intentions of the reserach are to consolidate ideas about the urgency of renewal as the only possible method of solving problems of a certain pattern of building, to determine criteria and measures for renewal and to determine rational or real directions for concrete contributions for the improvement of the standard of living, in short, to a new shift in living culture discussed settlement pattern.
Keywords: degradacija; prenova; Slovenia; Slovenija; stanovanja; stanovanjska naselja; večstanovanjske zgradbe; vrednotenje